2013
DOI: 10.7150/jca.5635
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Sequential Dual-Targeting Theragnostic Strategy (SMSDTTS): from Preclinical Experiments towards Possible Clinical Anticancer Applications

Abstract: Hitting the evasive tumor cells proves challenging in targeted cancer therapies. A general and unconventional anticancer approach namely small molecule sequential dual-targeting theragnostic strategy (SMSDTTS) has recently been introduced with the aims to target and debulk the tumor mass, wipe out the residual tumor cells, and meanwhile enable cancer detectability. This dual targeting approach works in two steps for systemic delivery of two naturally derived drugs. First, an anti-tubulin vascular disrupting ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 91 publications
1
15
0
Order By: Relevance
“…This selective tumor vascular targeting action has been demonstrated both in animal models [11,16,31,32] and human cancer patients [15,17,26,33]. Thus, tubulin depolymerizing class of medication represents novel chemotherapeutic agents that could be effective in the treatment of various forms of cancer.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This selective tumor vascular targeting action has been demonstrated both in animal models [11,16,31,32] and human cancer patients [15,17,26,33]. Thus, tubulin depolymerizing class of medication represents novel chemotherapeutic agents that could be effective in the treatment of various forms of cancer.…”
Section: Discussionmentioning
confidence: 94%
“…Further study is needed to fully define the mechanism behind this weaker effect of nitroglycerin in our hypertensive rat model. CA4P therapy has been shown to have promise in various clinical trials to treat advance cancers [4][5][6]26,32]. Previous study showed that CA4P significantly improved tumor response to radiation or thermoradiation, neither of which was influenced by the addition of anti-hypertensive agent, hydralazine [14].…”
Section: Discussionmentioning
confidence: 97%
“…Chemicals used-TsCl, Ti(O-iPr) 4 , n-BuLi, CuI, PPh 3 , Lindlar's catalysts and (trimethylsilyl)acetylene 30-were purchased from Sigma-Aldrich (St. Louis, MO, USA) or Alfa Aesar (GmbH, Karlsruhe, Germany). Dichlorobis(triphenylphosphine)palladium(II) was obtained as described in [31].…”
Section: Generalmentioning
confidence: 99%
“…CA-4 (1) shows strong cytotoxic activity against a wide variety of human cancer cell lines, including those that are multidrug resistant [2]. A water soluble disodium phosphate derivative of CA-4 (CA-4P, fosbretabulin) has shown promising results in human cancer clinical trials [3,4], thus stimulating significant interest in a variety of CA-4 analogues [5]. Different analogs of combretastatins are obtained, including heterocombretastatins containing heterocyclic fragments as rings A or B [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…As 131 I-Hyp preferentially accumulates in necrotic tissues, it delivers its radioactive energy to the adjacent living tumor remnants. 1,6,12 The b-particles emitted by 131 I-Hyp can kill living cells within 2.0 mm, and the g-rays produced by 131 IHyp aid in the detection of necrotic primary and metastatic tumors by means of nuclear imaging. Additionally, each treatment cycle may achieve long-term therapeutic efficacy and allow monitoring for weeks to months due to the eightday decay half-life of 131 I.…”
Section: Introductionmentioning
confidence: 99%